2022
DOI: 10.1155/2022/3585540
|View full text |Cite|
|
Sign up to set email alerts
|

miR-100-5p Is a Novel Biomarker That Suppresses the Proliferation, Migration, and Invasion in Skin Cutaneous Melanoma

Abstract: Description. Cutaneous melanoma (SKCM) is one of the most common skin malignancies. miR-100-5 has been found to highly express microRNAs in a variety of cancers. This is a novel biomarker to inhibit the proliferation, migration, and invasion of cutaneous melanoma. However, its function and potential mechanisms in SKCM remain unknown. Objective. To better understand the role and underlying mechanisms of SKCM, we conducted bioinformatics analysis and in vivo experiments. Results. We found its role as a tumor sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…[66] miR-100-5p can affect cell proliferation, migration, invasion, and apoptosis, including BC cells and SKCM cells. [67,68] miR-30b-5p significantly affects various biological processes including cell differentiation, oxidative stress, apoptosis, and protein stability. [69]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[66] miR-100-5p can affect cell proliferation, migration, invasion, and apoptosis, including BC cells and SKCM cells. [67,68] miR-30b-5p significantly affects various biological processes including cell differentiation, oxidative stress, apoptosis, and protein stability. [69]…”
Section: Discussionmentioning
confidence: 99%
“…[66] miR-100-5p can affect cell proliferation, migration, invasion, and apoptosis, including BC cells and SKCM cells. [67,68] miR-30b-5p significantly affects various biological processes including cell differentiation, oxidative stress, apoptosis, and protein stability. [69] miR-615-3p not only plays important roles in various tumor diseases and skeletal development, but has also been shown to be involved to some extent in neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%